(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2009)
Maize was collected from different markets of Bangladesh for the determination of ochratoxin A. Simultaneously controlled maize samples were analyzed to assess the ochratoxin A level of market samples and that of controlled samples. A total of 120 samples were analyzed to determine ochratoxin A including 70 market samples and 50 controlled samples. Market samples were found containing a high contamination level of ochratoxin A ranged from 1 to 117 Î¼g/kg and incidence rate was 40% whereas in the controlled samples the contamination rate was found very low ranged from 3 to 9 Î¼g/kg and the incidence rate was found 10% only. Key words: Maize, Ochratoxin A, Occurrence, Bangladesh, HPTLC Â doi: 10.3329/bjsir.v43i4.2239 Bangladesh J. Sci. Ind. Res. 43(4), 495-500, 2008